2022
DOI: 10.1101/2022.05.29.493850
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The SARS-CoV-2 accessory factor ORF7a downregulates MHC class I surface expression

Abstract: The pandemic caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has resulted in over 500 million infections and more than six million deaths worldwide. Although the viral genomes of SARS-CoV-1 and SARS-CoV-2 share high sequence homology, the clinical and pathological features of COVID-19 differ profoundly from those of SARS. It is apparent that changes in viral genes contribute to the increased transmissibility of SARS-CoV-2 and pathology of COVID-19. Cytotoxic T lymphocytes play a key role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 73 publications
0
7
0
Order By: Relevance
“…Given the functional consequence of localization of ORF7a we have observed, we suggest that studies employing C-terminally tagged ORF7a need to be interpreted with caution. However, a recent report that has not been peer-reviewed found that C-terminally tagged ORF7a was capable of down-regulating MHC-I in HEK293T cells ( 41 ) and that the C-terminal tail was not necessary for this function ( 42 ). While we expressed ORF7a-ARA in an inducible manner, the ORF7a in these two studies was transiently expressed, and we are investigating whether this or other mechanisms account for this difference.…”
Section: Discussionmentioning
confidence: 99%
“…Given the functional consequence of localization of ORF7a we have observed, we suggest that studies employing C-terminally tagged ORF7a need to be interpreted with caution. However, a recent report that has not been peer-reviewed found that C-terminally tagged ORF7a was capable of down-regulating MHC-I in HEK293T cells ( 41 ) and that the C-terminal tail was not necessary for this function ( 42 ). While we expressed ORF7a-ARA in an inducible manner, the ORF7a in these two studies was transiently expressed, and we are investigating whether this or other mechanisms account for this difference.…”
Section: Discussionmentioning
confidence: 99%
“…O R F 6 w a s i d e n t i fi e d a s a p o t e n t i a l immunomodulatory protein based on its role in targeting NLRC5, a critical transcriptional regulator of the gene coding for MHC I heavy chain (17). More recently, in bioRxiv-deposited articles, ORF3a and ORF7a were shown to reduce MHC I cell-surface expression via distinct mechanisms (13,14). ORF3a exerted a more general effect on suppressing the trafficking of proteins, including MHC I molecules, through the secretory pathway (13).…”
Section: Mhc Class I Antigen Presentationmentioning
confidence: 99%
“…ORF3a exerted a more general effect on suppressing the trafficking of proteins, including MHC I molecules, through the secretory pathway ( 13 ). On the other hand, ORF7a acted more specifically by associating with the MHC I heavy chain, possibly as a molecular mimic of β 2 m, thereby slowing the export of correctly assembled MHC I molecules out of the ER ( 13 , 14 ).…”
Section: Modulation Of Host Immune Functionsmentioning
confidence: 99%
See 1 more Smart Citation
“…To successfully establish infection and replicate in the host, many viruses have acquired the ability to inhibit MHC-I processing and presentation of viral antigens (14). Likewise, SARS-CoV-2 utilizes its viral proteins to interfere with the MHC-I pathway (15)(16)(17)(18)(19). SARS-CoV-2 ORF8 protein induces autophagic degradation of MHC-I and confers resistance to CTL surveillance (15).…”
Section: Introductionmentioning
confidence: 99%